IDENTIFIKASI KESULITAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG BILANGAN BULAT PADA SISWA SMP KRISTEN ENDE TAHUN PELAJARAN 2021/2022 - Yohana Benge; Natalia Peni; Konstantius Denny Pareira Meke (MEGA: Jurnal Pendidikan Matematika, 2021)
The purpose of this study was to determine the difficulties of students and the factors experienced by students in solving addition and subtraction problems of integers in seventh grade students of Ende Christian Middle School. The type of research used is descriptive qualitative research with data collection techniques using diagnostic tests, interviews, and documentation. The subjects of the research were the eighteenth grade students of Ende Christian Middle School as many as 22 students who completed the diagnostic test questions, there were 5 students whose data was taken to conduct interviews. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. From the data from interviews conducted, it shows that in solving problems students do not understand the concept of addition and subtraction of integers, and it is difficult to convert story questions into mathematical models and the factors that cause difficulties experienced by students in solving problems are the lack of willingness to learn from within students. themselves, students are often lazy to learn mathematics, do not want to listen to the teacher's explanation when the lesson is in progress, students do not concentrate fully during teaching and learning activities, students are afraid to ask the teacher when they do not understand the material being taught, students always assume that mathematics is very difficult, students are not careful when working on questions.